NGHIÊN CỨU CHẾ TẠO NHỰA EPOXY BIẾN TÍNH BẰNG THIOKOL LỎNG DÙNG ĐỂ SẢN XUẤT KEO DÁN TRONG NGÀNH HÀNG KHÔNG - Đỗ, Thị Thuỳ Trang; Phạm, Duy Nam; Vương, Văn Trường; Hoàng, Như Kha; Mai, Thị Nhâm (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
THE MANUFACTURE OF POLYSULFIDED MODIFIED EPOXY ADHESIVEThis study related to polysulfide modified epoxy resins and developing an adhesive from this modified resin. The composition comprises the copolymerization product of epoxy resin with polysulfide and polyester acrylate. Some mechanical properties of obtained adhesive has been enhanced such as tensile strength, chemical resistance and adhesion. The tested results have shown that the working life of the obtained adhesive is 125 mins, the tensile strength is 115 kgf/cm2, watter and oil resistances are good level. Such adhesive can be useful in a wide variety of application such as electrical and aviation adhesives.